Environmental Health Assessment of Tourism Area After the Covid-19 Pandemic - Reny Mareta Sari; Elizabeth Niha; Ukik Agustina; Niken Agus Tianingrum (Journal of Global Research in Public Health, 2022)
The closure of tourist attractions during the Covid-19 pandemic makes the facilities unmaintained and damaged so that it can endanger visitors. Safety and comfort are very important conditions in the tourism industry. Swimming pool is one of the tourist attractions that are found and visited by various age groups. Monitoring and assessment of the environmental health of the swimming pool area is very necessary to avoid the danger and risk of disease transmission to visitors. The study aimed to assess environmental health of the swimming pool after the Covid-19 pandemic. The assessment was conducted in Tirta Nirwana swimming pool. Environmental health assessment is carried out using a tourist attraction environmental health examination form. The assessment form consists of general environmental conditions and sanitation facilities which include clean water, public toilets, waste disposal, health promotion, and health facility. The environmental health assessment showed that the Tirta Nirwana swimming pool was declared healthy with good general condition and sanitation facility.